Volume and shape analysis of subcortical brain structures and ventricles in euthymic bipolar I disorder. Issue 3 (30th September 2015) - Quigley, Stephen J.; Scanlon, Cathy; Kilmartin, Liam; Emsell, Louise; Langan, Camilla; Hallahan, Brian; Murray, Michael; Waters, Conor; Waldron, Mairead; Hehir, Sarah; Casey, Helen; McDermott, Emma; et al.
Abstract: Previous structural magnetic resonance imaging (S-MRI) studies of bipolar disorder have reported variable morphological changes in subcortical brain structures and ventricles. This study aimed to establish trait-related subcortical volumetric and shape abnormalities in a large, homogeneous sample of prospectively confirmed euthymic bipolar I disorder (BD-I) patients ( n =60), compared with healthy volunteers ( n =60). Participants were individually matched for age and gender. Volume and shape metrics were derived from manually segmented S-MR images for the hippocampus, amygdala, caudate nucleus, and lateral ventricles. Group differences were analysed, controlling for age, gender and intracranial volume. BD-I patients displayed significantly smaller left hippocampal volumes and significantly larger left lateral ventricle volumes compared with controls. Shape analysis revealed an area of contraction in the anterior head and medial border of the left hippocampus, as well as expansion in the right hippocampal tail medially, in patients compared with controls. There were no significant associations between volume or shape variation and lithium status or duration of use. A reduction in the head of the left hippocampus in BD-I patients is interesting, given this region's link to verbal memory. Shape analysis of lateral ventricular changes in patients indicated that these are not regionally specific. Highlights: Large sample matched euthymic bipolar I disorder patients and healthy controls. Patients had decreased left hippocampal and increased left lateral ventricle volume. Patients had contraction of anterior head and medial border of left hippocampus. Patients had expansion of right hippocampal tail medially. Indicates presence of trait related neuroanatomical markers of bipolar disorder.